The ultra-lightweight support structure and gaseous helium cooling for the Mu3e silicon pixel tracker - Berger, Niklaus; Herkert, Adrian; Huxold, Lukas; Schöning, André; Wiedner, Dirk; Windelband, Bernd (Journal of Instrumentation, 2014)
The Mu3e experiment searches for charged lepton flavor violation in the rare decay μ→eee. In order to reach a sensitivity of better than 10−16, more than 109 muon decays per second have to be observed over a running time of one year. Precise determination of particle momentum, vertex position and time are necessary for background suppression. These requirements can be met by combining an ultra-lightweight tracker based on High-Voltage Monolithic Active Pixel Sensors (HV-MAPS) with a timing system which consists of a scintillating fiber detector and a tile hodoscope. As the momentum of particles from muon decay at rest is below 53 MeV/c, the silicon pixel tracker resolution is dominated by multiple Coulomb scattering. This leads to extreme requirements for the material budget of the tracking detector of below 0.1% of a radiation length per layer. Even though the target power consumption of the HV-MAPS detector is as low as 150 mW/cm2, the detector cooling must be very efficient and at the same time avoid adding material inside the active tracking volume.
Gesehen am 28.08.2020